Environment as the risk factor for tuberculosis in Malaysia: a systematic review of the literature - Nur Adibah Mohidem; Zailina Hashim; Malina Osman; Farrah Melissa Muharam; Saliza Mohd Elias; Rafiza Shaharudin (De Gruyter, 2024)
Reviews on Environmental Health, vol. 36, no. 4, 2021, pp. 493-499.